Predisposing factors for admission to intensive care units of patients with COVID-19 infection—Results of the German nationwide inpatient sample - Keller, Karsten; Farmakis, Ioannis T.; Valerio, Luca; Koelmel, Sebastian; Wild, Johannes; Barco, Stefano; Schmidt, Frank P.; Espinola-Klein, Christine; Konstantinides, Stavros; Münzel, Thomas; Sagoschen, Ingo; Hobohm, Lukas (Frontiers in Public Health, 2023)
Background Intensive care units (ICU) capacities are one of the most critical determinants in health-care management of the COVID-19 pandemic. Therefore, we aimed to analyze the ICU-admission and case-fatality rate as well as characteristics and outcomes of patient admitted to ICU in order to identify predictors and associated conditions for worsening and case-fatality in this critical ill patient-group. Methods We used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19 diagnosis in Germany between January and December 2020. All hospitalized patients with confirmed COVID-19 infection during the year 2020 were included in the present study and were stratified according ICU-admission. Results Overall, 176,137 hospitalizations of patients with COVID-19-infection (52.3% males; 53.6% aged ≥70 years) were reported in Germany during 2020. Among them, 27,053 (15.4%) were treated in ICU. COVID-19-patients treated on ICU were younger [70.0 (interquartile range (IQR) 59.0–79.0) vs. 72.0 (IQR 55.0–82.0) years, P < 0.001], more often males (66.3 vs. 48.8%, P < 0.001), had more frequently cardiovascular diseases (CVD) and cardiovascular risk-factors with increased in-hospital case-fatality (38.4 vs. 14.2%, P < 0.001). ICU-admission was independently associated with in-hospital death [OR 5.49 (95% CI 5.30–5.68), P < 0.001]. Male sex [OR 1.96 (95% CI 1.90–2.01), P < 0.001], obesity [OR 2.20 (95% CI 2.10–2.31), P < 0.001], diabetes mellitus [OR 1.48 (95% CI 1.44–1.53), P < 0.001], atrial fibrillation/flutter [OR 1.57 (95% CI 1.51–1.62), P < 0.001], and heart failure [OR 1.72 (95% CI 1.66–1.78), P < 0.001] were independently associated with ICU-admission. Conclusion During 2020, 15.4% of the hospitalized COVID-19-patients were treated on ICUs with high case-fatality. Male sex, CVD and cardiovascular risk-factors were independent risk-factors for ICU admission.